Annual World Bank Conference on Development Economics--Global 2010 : Lessons from East Asia and the Global Financial Crisis - Lin, Justin Yifu (World Bank, 2012)
The Annual World Bank Conference on Development Economics (ABCDE) is a forum for discussion and debate of important policy issues facing developing countries. The conferences emphasize the contribution that empirical economic research can make to understanding development processes and to formulating sound development policies. Conference papers are written by researchers in and outside the World Bank. This year's ABCDE included sessions on the following themes: industrial policy and development; social capital, institutions, and development; financial crisis and regulation; the road to a sustainable global economic system; and innovation and competition. In light of the global financial crisis, speakers touched on fundamental questions: what caused the current crisis, and how can the world economy recover?Are the standard prescriptions of development economics adequate to the task? Should developing countries alter their basic growth strategies? What is the proper role of the state? Should developing countries reexamine their commitment to free trade? How can global imbalances be rectified (especially between China and the United States)? Within the globalized financial system, how can regulation are improved? In attempting to answer these questions, many of the speakers searched for solutions in the lessons offered by the experience of Korea and other East Asian countries, which reacted with varying degrees of success to the financial crisis of the late 1990s. This volume includes selected papers from the conference as well as keynote addresses by SaKong, chairman of the Korean G-20 summit coordinating committee, and two distinguished economists: Anne Krueger, Stanford University and Johns Hopkins University, and Simon Johnson, Massachusetts Institute of Technology.